2022
DOI: 10.1161/jaha.122.026023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weight Loss on Early Left Atrial Myopathy in People With Obesity But No Established Cardiovascular Disease

Abstract: Background Obesity is associated with left atrial (LA) remodeling (ie, dilatation and dysfunction) which is an independent determinant of future cardiovascular events. We aimed to assess whether LA remodeling is present in obesity even in individuals without established cardiovascular disease and whether it can be improved by intentional weight loss. Methods and Results Forty‐five individuals with severe obesity without established cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Increased LA size as an early sign of LA remodeling, as shown in our study, might be an important link between obesity without cardiovascular comorbidities and HF, as deteriorations in LA structure and function of asymptomatic individuals have been shown to precede development of HF [ 61 ]. Our results also imply beneficial effects of dietary-induced weight loss on LA remodeling in healthy obesity suggesting that LA enlargement in early stages is at least partially reversible [ 39 ].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Increased LA size as an early sign of LA remodeling, as shown in our study, might be an important link between obesity without cardiovascular comorbidities and HF, as deteriorations in LA structure and function of asymptomatic individuals have been shown to precede development of HF [ 61 ]. Our results also imply beneficial effects of dietary-induced weight loss on LA remodeling in healthy obesity suggesting that LA enlargement in early stages is at least partially reversible [ 39 ].…”
Section: Discussionmentioning
confidence: 72%
“…CMR-FT studies in isolated obesity are rare. Deal, Rayner [ 39 ] observed GLS to be reduced in healthy obesity which was unaffected by dietary-induced weight loss. Likewise, another two studies found in their cross-sectional data a reduction of GLS and GCS in healthy people with obesity compared to healthy normal-weight controls [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a study conducted by Deal et al ., 24 obesity resulted in LA myopathy in obese individuals who did not have any obvious cardiovascular conditions. This LA myopathy includes LA enlargement and LA reservoir dysfunction.…”
Section: Discussionmentioning
confidence: 99%